Perancangan Sistem Informasi Akuntansi Laporan Keuangan Laba Rugi pada Restoran Eatboss Dengan Menggunakan PHP dan MySQL - Zilzi Zade Tazkia (Labkat Press KA FTIK UNIKOM, 2019)
This study aims to design a financial statement accounting information system application for Eatboss restaurant using the PHP and MySQL programming languages. The design of the financial statement accounting information system application in Eatboss restaurant using PHP and MySQL is done using library research and survey methods. At this time, it is necessary to prepare financial statements of profit and loss for each company, including restaurants, to find out the profit or loss gained during the specified period of the company. So that the company can determine the next decision for the continuity of better company activities.The design of fiinancial statement accounting information system in Eatboss reataurant using PHP and MySQL can facilitate omapnies in managing financial reports. With the maximum use of the financial statement accounting information system design at Eatboss restaurant using PHP and MySQL, it is expected that the company can more quickly and easily manage its financial statements based on accounting standards.